(untitled) (Scientific journal of the Fergana State University, 2023)
The aim of the article is to clarify the keeping problems of lexical-stylistic coloring in English translations of the novel "The Days Gone By"; Analysis of the specific features of artistic translation described in scientific works on translations from Uzbek to English and determination of methods of translation of lexical units with connotative meaning; To determine the ways of re-reflecting the stylistic features of the phraseological units used in the novel "The Days Gone By" in the translated text.